(untitled) (AYUSHDHARA, 2025)
Skin disorders are one of the major health issues in the present era. It is a multifaceted condition that includes the emotional and social impact on individuals, as it affects the psychological status of a person due to its appearance, severe itching, and disturbance to the daily routine. The prevalence of eczema is more common in rural areas than in urban ones. Eczema is an inflammatory reaction of the skin, characterized by variable itching and soreness, crusting, dryness, erythema, excoriation, exudation, fissuring, hyperpigmentation, lichenification, oozing, scaling, and vesiculation. No satisfactory treatment is available in contemporary medical practice except antihistamines and topical steroids. As it is a common chronic skin condition, it can lead to recurrent infections and poor quality of life if left untreated. The clinical features can be correlated to Vicharchika in Ayurveda, as it is characterized by Kandu, Srava, Pidaka, and Shyava Varna. It has been described under Kshudra Kushthas and is a Rakta Pradoshaja Vikara, involving three Doshas with Kapha predominance. A 36-year-old female patient presented with clinical features of diffuse hyperpigmented skin lesions on both lower limbs, associated with severe itching and a burning sensation for the past six years. The case was diagnosed as Vicharchika. The patient was treated following the principles of Rakta Pradoshaja Vikara (Kustha), i.e., Sroto Shodhana (purification of channels) and Dosha Shamana (pacification of doshas) Chikitsa, resulting in significant improvement in clinical symptoms.